2013
DOI: 10.1002/lary.23914
|View full text |Cite
|
Sign up to set email alerts
|

Histologic comparison of vocal fold microflap healing with sutures and glue

Abstract: The use of microsutures or fibrin glue to close microflap defects did not consistently improve vocal fold healing nor produce better scarring results when compared to healing by second intention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…The authors concluded that microflap closure via secondary intension provided better postoperative voice outcome . Other studies have reported that the performance of fibrin glue for vocal fold wound closure is unsatisfactory …”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The authors concluded that microflap closure via secondary intension provided better postoperative voice outcome . Other studies have reported that the performance of fibrin glue for vocal fold wound closure is unsatisfactory …”
Section: Introductionmentioning
confidence: 94%
“…The results showed that the suture treatment group had the highest collagen concentration, and the fibrin treatment group had the highest number of inflammatory cells. The study concluded that neither method was effective in either reducing scar formation or promoting wound healing relative to the no‐treatment group …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations